Changing course: the paradox of the career change student-teacher. Issue 5 (20th October 2018) - Varadharajan, Meera; Buchanan, John; Schuck, Sandy
Abstract: The article reports on career change student-teachers' (CCSTs) views and experiences regarding their teacher education programs in Australia. Data were collected through an online survey distributed to universities for dissemination to enrolled CCSTs in teacher education programs. The responses from over 500 CCSTs were analysed using an interpretive lens of inquiry and analysis. Over 80% of the responses indicated tensions and paradoxes that exist in CCSTs' lives as they come to terms with being students again. The article explores the impact on their student lives of the characteristics, experiences and expectations they bring to their studies, mediated by their previous careers and current circumstances. The findings discuss their perceptions of their teacher education programs and consider implications for CCSTs' professional learning needs in the light of the paradoxes that emerge from the data.